Fast Conversion of Three‐Particle Dicke States to Four‐Particle Dicke States with Rydberg Superatoms. Issue 4 (31st January 2023) - Liu, Ying‐Li; Ji, Yan‐Qiang; Han, Xue; Cui, Wen‐Xue; Zhang, Shou; Wang, Hong‐Fu
Abstract: Dicke states play an important role in quantum information processing and quantum computing. Here, by virtue of quantum Zeno dynamics and shortcuts to adiabaticity, a scheme for fast conversion of three‐particle symmetric Dicke states | D 3 ( k ) ⟩ $|D_{3}^{(k)}\rangle$ to four‐particle symmetric Dicke states | D 4 ( k ) ⟩ $|D_{4}^{(k)}\rangle$ ( k = 1, 2, 3 $k=1, 2, 3$ ) with Rydberg superatoms is proposed. This scheme can be completed within one step through adjusting the Rabi frequencies of classical fields. Moreover, the effect of decoherence induced by atomic spontaneous emission and leakage of the cavity on fidelities are considered. The numerical simulation demonstrates that this scheme has high fidelities and robustness against decoherence. Abstract : The implementation of entanglement among many atoms is a longstanding pursued goal in quantum computing and quantum information processing. Now a scheme for implementing the conversion of three‐particle Dicke states to four‐particle Dicke states with Rydberg superatoms is proposed by virtue of quantum Zeno dynamics and shortcuts to adiabaticity. Meanwhile, this scheme has high fidelities and robustness against decoherence.